GloPID-R report on chikungunya, o'nyong-nyong and Mayaro virus, part 5: entomological aspects - Pezzi, Laura; Jänisch, Thomas (Antiviral research, 2020)
The GloPID-R (Global Research Collaboration for Infectious Disease Preparedness) chikungunya (CHIKV), o’nyong-nyong (ONNV) and Mayaro virus (MAYV) Working Group has been established to investigate natural history, epidemiology and clinical aspects of infection by these viruses. Here, we present a report dedicated to entomological aspects of CHIKV, ONNV and MAYV. Recent global expansion of chikungunya virus has been possible because CHIKV established a transmission cycle in urban settings using anthropophilic vectors such as Aedes albopictus and Aedes aegypti. MAYV and ONNV have a more limited geographic distribution, being confined to Africa (ONNV) and central-southern America (MAYV). ONNV is probably maintained through an enzootic cycle that has not been characterized yet, with Anopheles species as main vectors and humans as amplification hosts during epidemics. MAYV is transmitted by Haemagogus species in an enzootic cycle using non-human primates as the main amplification and maintenance hosts, and humans becoming sporadically infected when venturing in or nearby forest habitats. Here, we focused on the transmission cycle and natural vectors that sustain circulation of these viruses in their respective locations. The knowledge of the natural ecology of transmission and the capacity of different vectors to transmit these viruses is crucial to understand CHIKV emergence, and to assess the risk that MAYV and ONNV will expand on wide scale using anthropophilic mosquito species not normally considered primary vectors. Finally, the experts identified knowledge gaps and provided adapted recommendations, in order to address future entomological investigations in the right direction.